Enzymatic Transesterification Of Palm Olein And Cod Liver Oil By Immobilized Rhizomucor Miehei And Pseudomonas Cepacia Lipases - Chew, Pauline Xui Sim (2001)
Enzymatic transesterification of palm olein (POo) and cod liver oil (CLO) in a solvent free system was studied using immobilized enzymes, with the aim of enriching POo with essential fatty acids/polyunsaturated fatty acids (PUF A) from CLO. The effects of enzyme loading, different ratio of POo and CLO blends, and the enzyme's regiospecificity on the triglyceride ( TG) profile and fatty acid composition were evaluated. Reverse-phase high performance liquid chromatography (HPLC) and alkaline titration evaluated the catalytic performance of the lipase in terms of degree of transesterification and hydrolysis, respectively. The fatty acid (FA) composition of glycerides was studied using gas chromatography (GC). The 1,3-specific and non-specific lipases used were Rhizomucor miehei lipase ( Lipozyme IM60) and Pseudomonas cepacia lipase, respectively. Results obtained show that the degree of transesterification and hydrolysis increased with an increase of R. miehei lipase concentration.The fatty acid composition based on relative concentrations of the mixtures before and after reaction showed no significant changes.